2019
DOI: 10.1002/jia2.25364
|View full text |Cite
|
Sign up to set email alerts
|

HIV, antiretroviral therapy and non‐communicable diseases in sub‐Saharan Africa: empirical evidence from 44 countries over the period 2000 to 2016

Abstract: Introduction The HIV‐infected population is growing due to the increased accessibility of antiretroviral therapy (ART) that extends the lifespan of people living with HIV (PLHIV). We aimed to assess whether national HIV prevalence and ART use are associated with an increased prevalence of cardiovascular risk factors. Methods Using country‐level data, we analysed the effect of HIV prevalence and use of ART on cardiovascular risk factors in 44 countries in sub‐Saharan Africa between 2000 and 2016. We used fixed‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 30 publications
(37 reference statements)
1
35
0
Order By: Relevance
“…Our ndings complement growing literature that supports integration of care for NCDs like HTN within existing HIV services by leveraging the huge gains attained by HIV programs [13][14][15][16][17]. Both PLHIV and healthcare providers expressed interest in integrated HTN/HIV care.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our ndings complement growing literature that supports integration of care for NCDs like HTN within existing HIV services by leveraging the huge gains attained by HIV programs [13][14][15][16][17]. Both PLHIV and healthcare providers expressed interest in integrated HTN/HIV care.…”
Section: Discussionsupporting
confidence: 66%
“…To preserve the gains made in HIV care, the treatment cascade must now be extended to include integration of care for HTN within existing HIV services for dual HTN and HIV control [13][14][15][16][17]. A multicenter trial in rural Uganda demonstrated that an integrated HTN/HIV care model that leverages the HIV infrastructure is preferable to vertical programs for both conditions [16].…”
Section: Introductionmentioning
confidence: 99%
“…systematic reviews outside SSA suggest that sexual minorities exhibit higher rates of NCDs [11]. Contrastingly, study findings from SSA point to comparably lower prevalence rates of NCDs (4.7%, 11.5% and 21.2%) among general population PLHIV clients [5,13,23,24].…”
Section: Plos Onementioning
confidence: 78%
“…pressure readings [28,29], several others point to an increased prevalence of hypertension and obesity [5,7,30]. There are mixed associations with ART use on the prevalence of NCDs with some studies suggesting no associations with hypertension [23,31] while others finding an increased odds for hypertension, dyslipidemia and other cardiovascular conditions [29,30,32]. Although chronic immune activation contributes to increased hypertension among PLHIV, the inflammatory milieu is poorly understood [33].…”
Section: Plos Onementioning
confidence: 99%
“…Other potential factors impacting on key issues such as adherence include concomitant co-morbidities such as infectious diseases appreciably increasing the pill burden and regimen complexity (Libby et al, 2013). Treatments for HIV can themselves also lead to weight gain and obesity further complicating the management of T2DM patients with HIV (Bailey et al, 2016;Pastakia et al, 2017;Kumar and Samaras, 2018;Coetzee et al, 2019;Venter et al, 2019). A study undertaken in an HIV clinic in South Africa found the metabolic syndrome was seen in 20% of cases within 1 year after initiation of anti-retroviral treatment (ART) despite the young age of patients, presumably as a consequence of ART exposure (Julius et al, 2011).…”
mentioning
confidence: 99%